Case report: severe adolescent major depressive syndrome turns out to be an unusual case of anti-NMDA receptor encephalitis - Moldavski, Alexander; Wenz, Holger; Lange, Bettina; Rohleder, Cathrin; Leweke, F. Markus (Frontiers in psychiatry, 2021)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a neuroinflammatory condition mediated by autoantibodies against the GluN1 subunit of the receptor. Clinically, it is characterized by a complex neuropsychiatric presentation with rapidly progressive psychiatric symptoms, cognitive deficits, seizures, and abnormal movements. Isolated psychiatric manifestations of anti-NMDAR encephalitis are rare and usually dominated by psychotic symptoms. We present a case of an 18-year-old female high school student - without a previous history of psychiatric disorders - with a rapid onset severe depressive syndrome. Surprisingly, we found pleocytosis and anti-NMDAR autoantibodies in the cerebrospinal fluid (CSF), despite an otherwise unremarkable diagnostic workup, including blood test, clinical examination, and cranial magnetic resonance imaging (MRI). After intravenous immunoglobulins treatment, a complete remission of the initial symptoms was observed. In a follow-up five years later, the young woman did not experience any relapse or sequelae. Anti-NMDAR encephalitis can present in rare cases as an organic disorder with major depressive symptoms without distinct concomitant psychotic or neurological symptoms. A clinical presentation such as a rapid onset of symptoms, distinct disturbance in the thought process, restlessness, and cognitive deficits should prompt screening for NMDAR- and other neural autoantibodies to rule out this rare but debilitating pathology.
Gesehen am 23.09.2021